Helmintofauna parasitária de Dasypus novemcinctus (Xenarthra: Dasypodidae) no sul do Rio Grande do Sul, Brasil - Gomes, Sâmara Nunes (2010)
Armadillos belong to the order Cingulata and are included in the superorder Xenarthra, which also belong to sloths and anteaters, hairy members of the order, which were restricted to the Neotropical region, occurring mainly in South America. Popularly known as nine banded armadillo, Dasypus novemcinctus occurs in the southern United States to South America, with wide distribution in Brazil. They are of great importance in the epidemiology of parasitc diseases, and potential disseminators of zoonoses. Since knowledge of helminths is important because it may assist in making decisions on future actions preservationists, as well as parasite control programs in these animals in captivity in zoos, therefore, the objective was to identify the helminths that parasitize Dasypus novemcinctus, in southern Rio Grande do Sul. The experiment consisted of examining 30 specimens of D. novemcinctus from the municipalities of Arambaré, Camaquã, Cristal, São Lourenço do Sul, Capão do Leão e Pinheiro Machado, taken with the permission of SISBIO / RS and trampled on the access roads to these towns. The animals were necropsied, had their organs removed, individually and separately analyzed by stereomicroscope to collect helminths. Parasites of the phylum Nematoda were identified as Bairdascaris dasypodina, Schneidernema retusa, Aspidodera ansirupa, A. binansata, A. fasciata, Physaloptera sp., Dipetalonema sp., Capillaria sp., Moennigia lutzi, M. Moennigi and M. filamentosus. Most nematodes were found in the small intestine, except for aspidoderids and S. retusa, which were present in the cecum. The cestode found was Mathevotaenia sp. and the acanthocephalan, Centrorhynchus sp. parasitizing both the small intestine. All nematodes are being cited for the first time in this host, in Rio Grande do Sul and cestode and acanthocephalan parasite have their first record in Dasypus novemcinctus in Brazil.